2002
DOI: 10.1128/mcb.22.5.1488-1494.2002
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Lethality Caused by Apoptosis during Gastrulation in Mice Lacking the Gene of the ADP-Ribosylation Factor-Related Protein 1

Abstract: ADP-ribosylation factor (ARF)-related protein 1 (ARFRP1) is a membrane-associated GTPase with significant similarity to the family of ARFs. We have recently shown that ARFRP1 interacts with the Sec7 domain of the ARF-specific guanine nucleotide exchange factor Sec7-1/cytohesin and inhibits the ARF/Sec7-dependent activation of phospholipase D in a GTP-dependent manner. In order to further analyze the function of ARFRP1, we cloned the mouse Arfrp1 gene and generated Arfrp1 null-mutant mice by gene targeting in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…This may reflect a nonspecific response, since a number of knockout mice show this effect (28). Alternatively, Miz1 might be involved in a survival pathway that relays adhesion-dependent survival signals to ectodermal cells.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect a nonspecific response, since a number of knockout mice show this effect (28). Alternatively, Miz1 might be involved in a survival pathway that relays adhesion-dependent survival signals to ectodermal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The functional importance of ARFRP1 is underscored by the finding that targeted disruption of the Arfrp1 gene in mice resulted in embryonic lethality at the gastrulation stage and apoptosis of ectodermal cells (Mueller et al, 2002). Studies in yeast have shown that Arl3p is required for recruitment of Arl1p and the GRIP domain-containing protein, Imh1p/Sys3p, onto the Golgi (Gangi Setty et al, 2003;Panic et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Rounded pyknotic cells within this area were only loosely attached to the ectodermal cell layer, and some apoptotic cells were found in the proamniotic cavity. This observation suggested that ARFRP1 plays a critical role in processes during early gastrulation such as adhesion-dependent morphogenesis, cytoskeletal reorganization, and/or development of cell polarity (11).…”
mentioning
confidence: 99%
“…Deletion of Arfrp1 in mice resulted in embryonic lethality (11). Arfrp1 Ϫ/Ϫ blastocysts implanted in vivo and formed egg cylinder-stage embryos that appeared normal until day 5.…”
mentioning
confidence: 99%